Effects of storage time and temperature on the protein fraction of aseptic milk - Joice Pranata; Dylan C. Cadwallader; MaryAnne Drake; David M. Barbano (Journal of Dairy Science)
ABSTRACT: Milk was collected on 2 different processing dates (2 replicates) at a commercial aseptic milk processing facility immediately as containers came off the processing line. Milk was heat treated by direct steam injection (142°C for 3 s) with flash vacuum cooling. Half of the packages of 1% fat aseptic milk were cooled immediately in ice to 4°C, and half were cooled to 21°C; both were stored at these respective temperatures for 12 mo, and a new package was opened and analyzed monthly for 12 mo by Kjeldahl analysis for nitrogen fractions, particle size analysis for protein aggregation, visual observation of gelation, and SDS-PAGE to determine proteolytic damage to casein. Differences were found in rates of gelation at the 2 storage temperatures, but the end results of milk gelation were the same. Protein settling in the aseptic milk formed a gel layer that stuck to the bottom of the packages and caused the remaining liquid product poured from the containers to decrease in protein concentration with time of storage. Quantitative SDS-PAGE analysis did not show evidence of proteolysis from native milk proteases or heat-stable microbial proteases during product storage. Thus, nonproteolytic changes in the milk were responsible for age gelation of this product. Lactosylation of κ-casein–whey protein complexes formed due to thermal treatment and Maillard browning may increase hydrophilicity of the complexes and cause them to dissociate from the surface of the casein micelles. With time of storage, the concentration of the lactosylated κ-casein–whey protein complex increased in the serum phase of the milk, whereas the gel was enriched in the more hydrophobic αS-casein and β-caseins.